2020
DOI: 10.1158/2326-6066.cir-19-0041
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tryptophan-Dioxygenase Activity Increases the Antitumor Efficacy of Immune Checkpoint Inhibitors

Abstract: ◥Tryptophan 2,3-dioxygenase (TDO) is an enzyme that degrades tryptophan into kynurenine and thereby induces immunosuppression. Like indoleamine 2,3-dioxygenase (IDO1), TDO is considered as a relevant drug target to improve the efficacy of cancer immunotherapy. However, its role in various immunotherapy settings has not been fully characterized. Here, we described a new small-molecule inhibitor of TDO that can modulate kynurenine and tryptophan in plasma, liver, and tumor tissue upon oral administration. We sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 82 publications
(118 reference statements)
3
71
0
Order By: Relevance
“…TDO was shown to be a promising therapeutic target to improve immune response to cancer cells (178). A recent study by Schramme et al demonstrated that TDO inhibition increases the antitumor efficacy of immune checkpoint inhibitors (179).…”
Section: Indoleamine 23-dioxygenase 2 Tryptophan 23-dioxygenase Amentioning
confidence: 99%
“…TDO was shown to be a promising therapeutic target to improve immune response to cancer cells (178). A recent study by Schramme et al demonstrated that TDO inhibition increases the antitumor efficacy of immune checkpoint inhibitors (179).…”
Section: Indoleamine 23-dioxygenase 2 Tryptophan 23-dioxygenase Amentioning
confidence: 99%
“…As an indication of the enzymatic activity of IDO1 and TDO, we measured kynurenine in the serum of pregnant mice (Figure 3). We showed in a previous report that circulating kynurenine in non-pregnant mice was produced by IDO1 and not by hepatic TDO, as it was completely absent in IDO1-KO mice, while it was slightly increased in TDO-KO mice in which tryptophan levels were elevated (30). We confirmed this result at early pregnancy time points, when serum kynurenine in TDO-KO mice was identical or slightly higher than in WT mice, while it was not detectable in double IDO1-TDO-KO mice.…”
Section: Discussionmentioning
confidence: 69%
“…In pathology, TDO is expressed by tumor cells of all hepatocarcinomas and 25% of glioblastomas, as well as by pericytes of vascular structures in focal spots of most late stage tumors, and by pericytes in pulmonary inflammatory lesions (27,28). TDO inhibition of either tumoral or hepatic TDO favors immune-mediated tumor rejection and increases the efficacy of immune checkpoint inhibitors (29,30). TDO was also identified in pericytes and interstitial syncytiotrophoblasts in the human placenta (27).…”
Section: Introductionmentioning
confidence: 99%
“…Tryptophan is the precursor of several active compounds, collectively named TRYCATs ( Figure 1 ). At the tumor microenvironment, TRP catabolism is promoted by indoleamine 2,3-dioxygenase (IDO1) overexpression under pro-inflammatory conditions, and it plays an important role in modulating antitumor immune response ( 18 20 ). In CRC, IDO1 expression at the tumor invasion front correlates with disease progression and worse clinical outcome ( 21 ) and is associated with the frequency of liver metastases ( 22 ).…”
Section: Introductionmentioning
confidence: 99%